Hydrophobic association supramolecular gel suitable for oil and gas drilling in fractured formation - Yongquan Han; Zhixue Yu; Zijun Guan; Rui Ma; Yuzhou Hu (Frontiers in Chemistry)
Supramolecular gel can be used to seal fractures and pores in the formation during oil and gas drilling and production. In this study, a supramolecular gel plugging agent based on hydrophobic association was prepared by free radical polymerization of acrylamide, octadecyl methacrylate, sodium dodecyl sulfate and other monomers by micellar copolymerization. The forming time, rheology, swelling, mechanical properties and plugging properties of supramolecular gels were studied. The experimental results show that the formation time of supramolecular gel plugging agent is controllable, and it has excellent viscoelastic recovery ability in a certain range of shear strain and scanning frequency. When the compression amount is close to 88.3%, the compressive stress reaches 3.82 MPa. Meanwhile, the swelling performance of supramolecular gel was good, and the equilibrium swelling degree reached 22.1% after 188 min swelling in 15% NaCl brine solution. In 1% NaCl solution, the equilibrium swelling degree of supramolecular gel reached 32.5%. In addition, supramolecular gel has strong formation bonding ability, good plugging performance, plugging rate is greater than 95%, can effectively reduce the leakage and improve the plugging effect of low permeability layer. It is of reference and guiding significance for the long-term plugging of heterogeneous and malignant leakage formations.